FABP5, a Novel Immune-Related mRNA Prognostic Marker and a Target of Immunotherapy for Multiple Myeloma - Jia, Haipeng; Zhang, Xiaofen; Liu, Xinxin; Qiao, Ruifang; Liu, Yan; Lv, Sulong; Zhu, Hongbo; Wang, Jie; Kong, Qiuhong; Zhang, Hong; Zhang, Zhirong (Frontiers in Medicine, 2021)
Objective: Multiple myeloma is an incurable hematological malignancy. It is imperative to identify immune markers for early diagnosis and therapy. Here, this study analyzed immune-related mRNAs and assessed their prognostic value and therapeutic potential. Methods: Abnormally expressed immune-related mRNAs were screened between multiple myeloma and normal bone marrow specimens in the GSE47552 and GSE6477 datasets. Their biological functions were then explored. Survival analysis was presented for assessing prognosis-related mRNAs. CIBERSORT was utilized for identifying 22 immune cell compositions of each bone marrow specimen. Correlation between FABP5 mRNA and immune cells was then analyzed in multiple myeloma. Results: 31 immune-related mRNAs were abnormally expressed in multiple myeloma, which were primarily enriched in B cells-related biological processes and pathways. Following validation, FABP5 mRNA was a key risk factor of multiple myeloma. Patients with its up-regulation usually experienced unfavorable outcomes. There were distinct differences in the infiltration levels of B cells naïve, B cells memory, plasma cells, T cells CD4 naïve, resting memory CD4 T cells, activated memory CD4 T cells, Tregs, resting NK cells, M0 macrophages, M1 macrophages, M2 macrophages and neutrophils between multiple myeloma and normal samples. FABP5 mRNA had correlations to B cells memory, B cells naïve, dendritic cells activated, macrophages M0, macrophages M1, macrophages M2, neutrophils, activated NK cells, resting memory CD4 T cells, CD8 T cells and Tregs. Conclusion: Collectively, our data showed that FABP5 mRNA was related to immune microenvironment, which could be a target of immunotherapy and prognostic marker for multiple myeloma.